Monitor feedback versus instructor feedback for post-pandemic basic life support training: a randomized controlled trial among dental students - Shusei Yoshimine; Kaoru Yamashita; Yurina Higa; Akari Uto; Mitsutaka Sugimura (BMC Medical Education)
Abstract Background Dentists must provide basic life support (BLS) until the arrival of emergency services. Improving educational quality and expanding training opportunities in dental schools can enhance patient survival rates. Traditionally, primary life support training for dental students was conducted in person; however, in-person practice has become challenging during the recent coronavirus disease (COVID-19) pandemic caused by the novel coronavirus. Our objective was to examine how monitor feedback from a cardiopulmonary resuscitation (CPR) simulator and monitoring equipment, versus instructor feedback, affects the quality of BLS training for dental students, and to evaluate effective self-study methods during the pandemic. Methods All participants (n = 40) underwent a pretraining test to assess their baseline technical skills in providing CPR. The students were then randomly divided into the following two groups: monitor feedback and instructor feedback. After the training, a post-test was administered using the same method as that used for the pretest. We statistically analyzed changes in chest compression (CC) depth, CC rate, CC fraction, and tidal volume before and after training in the two groups. Results The analysis included 34 participants (17 per group) after excluding those lost to attrition. In the monitor feedback group, compared with the pretest, the post-test revealed a significantly improved CC depth. Meanwhile, the CC rate improved significantly in the instructor feedback group. Regarding CC depth, monitor feedback led to improved compression depth compared to instructor feedback. Conversely, instructor feedback on the CC rate led to superior results compared to monitor feedback. Conclusions Training programs should provide monitor feedback for CC depth and instructor feedback on the CC rate to establish more effective self-study training methods. Different feedback types influence specific aspects of CPR and that further validation is required.